Comparison of the Effectiveness of Mindfulness Training and Social Competence Training on Aggression among Sixth-Grade Male Students in Tabriz - Maleki, Bita; Hoseini Nasab, Seyed Davoud; Panahali , Amir (Mental Health and Lifestyle Journal, 2025)
The aim of the present study was to compare the effectiveness of mindfulness training and social competence training on aggression among sixth-grade male students in Tabriz. The research method was quasi-experimental using a pretest–posttest design with a control group. The statistical population included adolescent boys studying in the sixth grade in Tabriz during the 2023–2024 academic year. From this population, 90 boys were selected through multi-stage cluster random sampling and randomly assigned to two experimental groups and one control group (30 participants in each group). The first experimental group received an eight-session, 75-minute mindfulness training program, while the second experimental group received an eight-session, 75-minute social competence training program. All three groups were assessed in both the pretest and posttest stages using the Eysenck and Glynn Wilson Aggression Questionnaire. Data were analyzed using analysis of covariance (ANCOVA) and the LSD post hoc test to examine intergroup differences. The results indicated that both mindfulness training and social competence training led to a reduction in aggression among male students. Furthermore, the findings revealed a significant difference between the effectiveness of social competence training and mindfulness training in reducing aggression, with social competence training exerting a greater effect. It can be concluded that both mindfulness and social competence training are effective in reducing aggression among students, although their levels of effectiveness differ.